2010
DOI: 10.1095/biolreprod.109.080440
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Dual Specificity Phosphatase 1 (DUSP1) by Gonadotropin-Releasing Hormone (GnRH) and the Role for Gonadotropin Subunit Gene Expression in Mouse Pituitary Gonadotroph LbetaT2 Cells1

Abstract: We examined the expression of dual specificity phosphatase 1 (DUSP1) by gonadotropin-releasing hormone (GnRH) stimulation and investigated the role of DUSP1 on gonadotropin gene expression using LbetaT2 gonadotroph cell line. DUSP1 expression was markedly increased 60 min after GnRH stimulation, and mitogen-activated protein kinase 3/1 (MAPK3/1) activation was gradually decreased after 60 min. GnRH-induced MAPK3/1 activation was completely inhibited by U0126, a MEK inhibitor, whereas GnRH-induced DUSP1 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 56 publications
3
16
0
Order By: Relevance
“…We previously demonstrated that after 12 h of exposure to GnRH pulses, DUSP1 was expressed following high-frequency pulsatile GnRH stimulation but not after low-frequency GnRH pulses [16]. Here, we again confirmed the frequency-dependent induction of DUSP1 expression by pulsatile stimulation of GnRH.…”
Section: Effect Of Pulsatile Gnrh Stimulation On Dusp1 Expressionsupporting
confidence: 84%
See 3 more Smart Citations
“…We previously demonstrated that after 12 h of exposure to GnRH pulses, DUSP1 was expressed following high-frequency pulsatile GnRH stimulation but not after low-frequency GnRH pulses [16]. Here, we again confirmed the frequency-dependent induction of DUSP1 expression by pulsatile stimulation of GnRH.…”
Section: Effect Of Pulsatile Gnrh Stimulation On Dusp1 Expressionsupporting
confidence: 84%
“…In separate experiments, we demonstrated that upon pulsatile GnRH stimulation, DUSP1 expression was observed following high-but not lowfrequency GnRH pulses [16], suggesting that DUSP1 may have physiological functions that determine GnRH pulse frequency-dependent differential stimulation of Lhb and Fshb gene expression levels in gonadotrophs.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Triptolide, a diterpenoid isolated from the Chinese herb Tripterygium wilfordii hook f, has been shown to inhibit DUSP1 induction in various cell types treated with different stimuli (5,46,64). Therefore, we investigated the effect of triptolide and Stx1 treatments on MAPK activation.…”
Section: Cytokine and Chemokine Expression Kinetics Induced By Stx1 Tmentioning
confidence: 99%